What curriculum? Which methods? A cluster randomized controlled trial of social and financial education in Rwanda. (November 2017) - Shephard, Daniel D.; Kaneza, Yves V.; Moclair, Paul
Abstract: Life-skills based financial education (LSFE) for young people is one potential intervention for improving the financial capabilities of a population. However, the pedagogical methods for LSFE have rarely been studied. This study represents the first cluster randomized controlled trial to analyze both student outcomes and the observed use of active learning methods (ALMs) by teachers. The study further tested the power of Social Cognitive Theory (SCT) to explain the outcomes of a LSFE program that contains explicit personal and social components that link to SCT. The study was undertaken by randomizing 50 schools in Rwanda that had been stratified across 5 districts: Huye, Karongi, Nyagatare, Nyanza, and Ruhango. It comprised 250 teachers with a mean age of 31.8 (SD = 6.2) and 1750 students with a mean age of 15.0 (SD = 2.6). The intervention increased teachers' observed use of ALMs as well as the average time on task of the students observed in class. Students in the treatment group also exhibited increased self-reported active learning environments, general self-efficacy, general financial capability, and self-reported savings behavior. Less robust results indicated the intervention increased students' planning attitudes and decreased their self-reported behavioral and cognitive engagement. Highlights: A participatory teacher training with local trainers improved teachers' pedagogy. Teacher training and a life-skills program increased students' time on task in class. A social and financial program with active learning methods improved self-efficacy. Afterwards students had better financial capabilities and savings behavior.